Las variaciones de Hegel : sobre la "Fenomenología del espíritu" - Jameson, Fredric; Sánchez Usanos, David; Jameson, Fredric (Tres Cantos, Madrid, España : Ediciones Akal, S.A., 2015)
In this major new study, philosopher and cultural theorist Fredric Jameson offers an innovative reading of a book that forms part of the bedrock of modern Western thought Hegers Phenomenology of Spirit.
Includes bibliographical references.
Online resource; title from ePub title page (Digitalia, viewed February 15, 2017)
Keywords: Hegel, Georg Wilhelm Friedrich, -- 1770-1831. -- Criticism and interpretation; Phenomenology; Spirit; Electronic books